Assessment of Knowledge and Practice regarding the Prevention of Surgical Site Infection (SSI) among Nursing Staff at DHQ-Teaching Hospital, KDA Kohat and Liaqat Memorial Hospital Kohat - Muhammad Umair; Muhammad Younas; Muhammad Jasim; Muhammad Bilal; Mujahid Khan; Azeemullah; Aftab Ahmad; Muhammad Ilyas (International Journal of Medical and Health Research, 2026)
Among the most common infections associated with health care, surgical site infections are still the biggest cause of increased morbidity, prolonged hospital stays, mortality, and cost. By employing evidence-based infection prevention strategies, nursing staff can greatly lessen SSIs. Therefore, assessing their expertise and methods is important to enhance patients' and healthcare outcomes. The aim of this study was to assess the knowledge and behaviors of nursing staff members about surgical site infection prevention in DHQ Hospital KDA and Liaqat Memorial Hospital, Kohat. The study objectives included: (1) To assess the level of knowledge of nursing staff regarding the prevention of surgical site infections, and (2) To determine the preventive practices used by nursing staff in the prevention of surgical site infections. From January to July 2026, the nurses working in selected Kohat hospitals were involved in this quantitative descriptive cross-sectional study. (86) Participants were enrolled through a convenience sampling technique. For data collection, a structured questionnaire consisting of 20 questions about knowledge, 25 statements about practice, and demographic data was used. SPSS version 27 was used for the analysis of collected data. The results were summarized by using descriptive statistics such as frequencies, percentages, means, and standard deviations. The total number of participants was 86, out of which (45.3%) were women and (54.7%) were men. Most of the participants (44.2%) had 1 – 5 years of clinical experience, (44.2%) of them were between the ages of 20 and 29, and (40.7%) of them had a BSN degree. (55.8%) of the participants reported that they had not received formal training in SSI prevention. Results showed that the participants' level of knowledge regarding preventing surgical site infections was generally good, with one item of knowledge having the highest rate of correct responses, which was 94.2%. Furthermore, nursing staff demonstrated good preventive procedures, particularly in areas such as hand hygiene, using sterile dressing materials, aseptic techniques, disposing of contaminated materials properly, and keeping an eye on surgical wounds. However, there is still room for improvement because some gaps in knowledge and practice related to body mass index evaluation and preoperative patient education were found. Findings of the study revealed that the prevention of surgical site infections, nursing staff at DHQ Hospital KDA and Liaqat Memorial Hospital, Kohat, showed satisfactory practices as well as good expertise. Although the results revealed some positive outcomes, a large proportion of the participants did not receive formal training in SSIs. The results of the knowledge questions also showed certain gaps. Therefore, to further reduce the incidence of SSIs and enhance patient safety, ongoing professional development is needed, along with regular in-service training and strict adherence to evidence-based infection prevention guidelines.